2017
DOI: 10.4103/0976-3147.193553
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Patients are at Risk of Cardiac Arrhythmias: A Novel Approach using QT-nomogram, Tachogram, and Cardiac Restitution Plots

Abstract: Background:Sudden death is reported in patients who had a history of epilepsy and some authors believed that is due to cardiac arrhythmias.Objectives:This study aimed to predict that the epileptic patients are at risk of serious cardiac arrhythmias by QT-nomogram, tachogram (Lorenz), and cardiac restitution plots.Methods:A total number of 71 healthy subjects (Group I) and 64 newly diagnosed epileptic patients (Group II) were recruited from Al-Yarmouk and Baghdad Teaching hospitals in Baghdad from March 2015 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The burden of other subtypes of arrhythmia in epilepsy patients is shown in detail in Figure 1 . Many arrhythmia subtypes have been associated with epilepsy patients [ 3 , 8 - 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of other subtypes of arrhythmia in epilepsy patients is shown in detail in Figure 1 . Many arrhythmia subtypes have been associated with epilepsy patients [ 3 , 8 - 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, heart rate is also an important marker to prevent serious cardiac morbidity in epilepsy. Such variations should not be neglected as it can have hazardous consequences [ 3 - 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by other authors [5,13] while other authors reported similar QTc interval durations in both groups [28,29] . However, a significant increase in QTc values were reported in other studies among epileptic patients compared to the control group [30,31] .…”
Section: Qtc and Cardiac Arrhythmic Changesmentioning
confidence: 79%
“…Both measures performed better than time-domain heart rate variability analysis. Most recently, restitution has been used in a rural setting as a readily available way of assessing arrhythmia liability in epileptic patients (Al-Nimer, Al-Mahdawi, & Abdullah, 2017). In a study comparing 71 healthy subjects versus 64 newly diagnosed epileptic patients, QT nomograms did not disclose significant findings while restitution steepness showed that epileptic patients were vulnerable.…”
Section: Other Usesmentioning
confidence: 99%